The Effect of the "Less Waste, More Coffee" Campaign towards Increasing Green Awareness of Indonesian Work Coffee Consumers - Salsabila, Shyiva Sarah; Astuti, Sri Wahyuning (Jurnal Ilmiah Komunikasi Makna, 2024)
This research aims to determine the effect of the "Less Waste, More Coffee" campaign on increasing green awareness of Work Coffee Indonesia consumers. The population in this research is Indonesian Work Coffee consumers with specified criteria. The sampling method uses accidental sampling technique. Types of primary and secondary data using simple linear regression analysis techniques. The results of descriptive data research on the campaign variable (X) show a magnitude of 83.69% and the green awareness variable shows a magnitude of 79.42%, which means that both variables are rated high based on the position of the continuum line. In the t hypothesis test, it was found that each independent variable and dependent variable had an influence. So, the campaign was proven to have an effect on increasing green awareness with an overall significance level of 0.000 (0.000 < 0.05) and it was found that H0 was rejected and H1 was accepted. So the campaign has an effect on increasing green awareness of Work Coffee Indonesia consumers.